"They're all going out to something weird": workflow, legacy and metadata in the music production process - McGarry, Glenn; Tolmie, Peter; Benford, Steve; Greenhalgh, Chris; Chamberlain, Alan (ACM, 2017)
In this paper we use results from two ethnographic studies of the music production process to examine some key issues regarding how work is currently accomplished in studio production environments. These issues relate in particular to workflows and how metadata is adapted to the specific needs of specific parts of the process. We find that there can be significant tensions between how reasoning is applied to metadata at different stages of production and that this can lead to overheads where metadata has to be either changed or created anew to make the process work. On the basis of these findings we articulate some of the potential solutions we are now examining. These centre in particular upon the notions of Digital/Dynamic Musical Objects and flexible metadata shells.